Perbedaan Daya Antibakteri Ekstrak Temulawak (Curcuma xanthorrhiza Roxb.) 3,125% dan Chlorhexidine 0,2% terhadap Lactobacillus acidophilus - Nanik Zubaidah; Devi Eka Juniarti; Firza Basalamah (Conservative Dentistry Journal, 2018)
Background: Caries is a process of demineralization of hard tissues of teeth due to the activity of bacterial metabolism. Lactobacillus acidophilus as one of the cariogenic bacteria that important process of deep caries. Efforts that can be used to inhibit cariogenic bacteria for example using antibacterial agents such as chlorhexidine that have been shown to inhibit Lactobacillus acidophilus bacteria, but chlorhexidine has some side effects. It takes basic herbal ingredients as an alternative agent that can inhibit the growth of cariogenic microorganisms, one of them is temulawak extract. Purpose: This research was conducted to compare antibacterial agent between Curcuma xanthorrhizaRoxb and chlorhexidine 0,2% to inhibit Lactobacillus acidophilus. Methods: The research was a laboratory experimental study. Temulawak extract was made by maceration method with etanol 96% and certain dilution was performed to obtain concentration of temulawak extract 100%, 50%, 25%, 12,5%, 6,25%, 3,125%, 1,56%, 0,781%. A preliminary study was conducted to determine the value of KHM and KBM of temulawak extract against Lactobacillus acidophilus were known by counting the growth of bacteria colonies on muellerhinton media in CFU/ml. From the calculation of the number of colonies Lactobacillus acidophilus, obtained KHM value of 3.125% and KBM value of 6.25%. Further research is conducted by comparing antibacterial ability of temulawak extract used KHM concentration and chlorhexidine 0,2% by using diffusion method by measurement of inhibiton zoneResult: Measurement result of inhibition zone by using calipers show that chlorhexidine 0,2% have inhibiting zone (in mm) 15.1; 15.2; 15.4; 14.9; 15.0; 15,15; 15.5; 15.7; 15.8; 16.0; 14.6; 15.2; 14,85; 15,1; 15.3; 15,2, while the measurement of inhibition zone of temulawak extract 3,125% are (in mm) 10,0; 10.3; 10.2; 9.9; 9.8; 10.1; 10.3; 10.1; 10.45; 10.1; 9.95; 9.85; 8.85; 9.35; 9.45; 9.4. Conclusion: Chlorhexidine 0,2% more potential as antibacterial agent than temulawak extract 3.125% to inhibit Lactobacillus acidophilus.